The Metabolism of Separase Inhibitor Sepin-1 in Human, Mouse, and Rat Liver Microsomes - Li, Feng; Zhang, Nenggang; Gorantla, Siddharth; Gilbertson, Scott R.; Pati, Debananda (Frontiers in Pharmacology, 2018)
Abstract Separase, a known oncogene, is widely overexpressed in numerous human tumors of breast, bone, brain, blood, and prostate. Separase is an emerging target for cancer therapy, and separase enzymatic inhibitors such as sepin-1 are currently being developed to treat separase-overexpressed tumors. Drug metabolism plays a critical role in the efficacy and safety of drug development, as well as possible drug-drug interactions. In this study, we investigated the in vitro metabolism of sepin-1 in human, mouse, and rat liver micrsomes using metabolomic approaches. In human liver microsomes, we identified 7 metabolites including one cysteine-sepin-1 adduct and one glutathione-sepin-1 adduct. All the sepin-1 metabolites in HLM were also found in both mouse and rat liver microsomes. Using recombinant CYP450 isoenzymes, we demonstrated that multiple enzymes contributed to the metabolism of sepin-1, including CYP2D6 and CYP3A4 as the major metabolizing enzymes. Inhibitory effects of sepin-1 on seven major CYP450s were also evaluated using the corresponding substrates recommended by the US Food and Drug Administration (FDA). Our studies indicated that sepin-1 moderately inhibits CYP1A2, CYP2C19, and CYP3A4 with IC50 < 10 M but weakly inhibits CYP2B6, CYP2C8/9, and CYP2D6 with IC50 > 10 M. This information can be used to optimize the structures of sepin-1 for more suitable pharmacological properties and to predict the possible sepin-1 interactions with other chemotherapeutic drugs.